INTELLECTUAL DISABILITY CLASSIFICATION, CAUSES, EPIGENETIC MECHANISMS AND TREATMENT - ANJUM, R; REHMAN, AU; MAQSOOD, H; ILYAS, U; NIAZ, M; ROHAIL, .; MOHSIN, S; JURRAT, H; ANJUM, S; MUNAWAR, I; et al. (Biological and Clinical Sciences Research Journal, 2023)
Intellectual disability (ID) is a condition characterized by defective adaptive and cognitive attitude that can occur with various mental disorders, such as attention deficit/hyperactivity and autism spectrum disorder. It may also be associated with malformation syndromes affecting other organs. Genetic studies have linked several chromatin-modifying enzymes and epigenetic regulators to ID disorders (IDDs). This review explores how dysfunction in histone modifiers, chromatin remodelers, and methyl-DNA binding proteins can cause neurodevelopmental deformities and alter brain plasticity. The use of mouse models generated through human genetics has allowed researchers to uncover the molecular basis of ID and explore potential therapeutic strategies. Understanding the chromatin regulators associated with IDDs has broader implications for treating other IDDs, as they target common downstream genes and cellular functions. Investigating these disorders can also shed light on the function of chromatin regulators in brain growth, plasticity, and gene regulation, leading to new insights into fundamental questions in neurobiology.